Konsep Kebahagiaan menurut Islamic Worldview dan menurut Orang yang Berpandangan bahwa Kehidupan Hanyalah di Dunia - Masithoh, Fisa Bela; Hudallah, Hudallah; Isrofuzain, Isrofuzain; Sumiran, Sumiran (TSAQOFAH, 2025)
Worldview is generally understood as a philosophy or life principle held by individuals, nations, cultures, or civilizations. When related to culture, the meaning of worldview adjusts to the characteristics of that culture, ultimately shaping one’s perception of existence and reality. Dominant factors in the formation of a worldview may stem from philosophy, religion, belief systems, or specific social value structures. Differences in these factors generate a spectrum of perspectives, ranging from those focused solely on worldly aspects to those encompassing metaphysical dimensions. As a framework, worldview comprises fundamental aspects that serve as benchmarks for interpreting life. In this regard, Syed Muhammad Naquib al-Attas identifies nine core components of the Islamic worldview: God, revelation (al-Qur’an), creation (the universe), the human soul, knowledge, religion, freedom, values and virtues, and happiness. Islam as a worldview offers a complete, eternal, and transcendent value system that, when adopted as a life guide, directs individuals toward true happiness in both this world and the hereafter. This paper aims to examine how Islam as a worldview shapes human attitudes and life orientations. The study employs a qualitative method with a literature review approach based on various relevant sources. The findings indicate that the Islamic worldview can serve as a comprehensive life framework for navigating the complexities of modern life.